Pre-Marriage Pregnancy in Islamic Law Compilation (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
The aim of this paper is to discuss pre-marriage pregnancy in Islamic Law Compilation. This study is literature review research with qualitative method. The data was gathered through content analysis and written material. Data analysis was analyzed using grounded theory approach and thematic building. The results showed that the formulation of article 53 paragraph (1), of the Islamic Law Compilation, a pregnant woman can be married with the man who impregnated her. And article 53 provides a solution for pregnant women who are married to men who impregnate them. While in relation to the status of child, it is considered legal because there has been a legal marriage; however, in the sharia, the status of child is still debated. Regarding the issue of which opinion is used, it can be seen from which opinion is greater for the benefit of society.